Gain improvement in a dual-stage S-band EDFA by filtration of forward C-band ASE - Harun, Sulaiman Wadi; Zulkifli, Mohd Zamani; Tamjis, Mohamad Rom; Ahmad, Harith (Taylor & Francis, 2008)
Gain improvement in a dual-stage S-band erbium-doped fiber amplifier (S-band EDFA) is demonstrated using a broadband fiber Bragg grating (FBG) operating in the conventional-band (C-band) region or a C-band/S-band wavelength division multiplexing (WDM) coupler which filters out the forward C-band amplified spontaneous emission (ASE) in the amplifier system, thus increasing the population inversion in the S-band region. The gain for the amplifier with the WDM coupler increases by about 8.5 dB with an input signal power of -40 dBm, compared to that of the conventional dual-stage amplifier. The gain improvement varies from 4.0-9.2 dB at a wavelength region between 1480 to 1512 nm without a significant noise figure penalty.